Grazing effects on vegetation dynamics in the savannah ecosystems of the Sahel - Haftay Hailu Gebremedhn; Ousmane Ndiaye; Sylvanus Mensah; Cofélas Fassinou; Simon Taugourdeau; Torbern Tagesson; Paulo Salgado (Ecological Processes, 2023)
Abstract Background The savannah ecosystems of Sahel have experienced continuous and heavy grazing of livestock for centuries but still, their vegetation response to grazing pressure remains poorly understood. In this study, we analysed the herbaceous plant dynamics, measured by species diversity, composition, cover, and biomass in response to grazing pressure in the savannah ecosystems of Sahel. In Senegal, we selected four savannah sites represented with high, moderate, light and no grazing intensity levels. Transect survey methods were used for sampling the vegetation data within each of the sites. Species richness and composition were analysed using species accumulation curve and multivariate analyses. Furthermore, we used General Linear Models and a piecewise Structural Equation Model (pSEM) to examine the relationships between grazing intensity, vegetation cover, diversity and biomass. Results The herbaceous species diversity and composition varied significantly among the different grazing intensity levels (p <0.001). The plant species composition shifted from the dominance of grass cover to the dominance of forb cover with increasing grazing pressure. Moreover, the attributes of species diversity, herbaceous biomass, and ground cover were higher on sites with low grazing than sites with high and moderate grazing intensity. Across all sites, species diversity was positively related to total biomass. The pSEM explained 37% of the variance in total biomass and revealed that grazing intensity negatively influenced total biomass both directly and indirectly through its negative influence on species diversity. Conclusions Managing grazing intensity may lead to higher plant production and higher mixed forage establishment in the dryland savannah ecosystems. This information can be used to support land management strategies and promote sustainable grazing practices that balance the needs of livestock with the conservation of ecosystem health and biodiversity.